A brief history of the Major Rickettsioses in the Asia-Australia-Pacific region: A capstone review for the special issue of TMID - Paris, DH; Kelly, DJ; Fuerst, PA; Day, NPJ; Richards, AL (MDPI, 2020)
The rickettsioses of the “Far East” or Asia–Australia–Pacific region include but are not limited to endemic typhus, scrub typhus, and more recently, tick typhus or spotted fever. These diseases embody the diversity of rickettsial disease worldwide and allow us to interconnect the various contributions to this special issue of Tropical Medicine and Infectious Disease. The impact of rickettsial diseases—particularly of scrub typhus—was substantial during the wars and “police actions” of the last 80 years. However, the post-World War II arrival of effective antibiotics reduced their impact, when recognized and adequately treated (chloramphenicol and tetracyclines). Presently, however, scrub typhus appears to be emerging and spreading into regions not previously reported. Better diagnostics, or higher population mobility, change in antimicrobial policies, even global warming, have been proposed as possible culprits of this phenomenon. Further, sporadic reports of possible antibiotic resistance have received the attention of clinicians and epidemiologists, raising interest in developing and testing novel diagnostics to facilitate medical diagnosis. We present a brief history of rickettsial diseases, their relative importance within the region, focusing on the so-called “tsutsugamushi triangle”, the past and present impact of these diseases within the region, and indicate how historically, these often-confused diseases were ingeniously distinguished from each another. Moreover, we will discuss the importance of DNA-sequencing efforts for Orientia tsutsugamushi, obtained from patient blood, vector chiggers, and rodent reservoirs, particularly for the dominant 56-kD type-specific antigen gene (tsa56), and whole-genome sequences, which are increasing our knowledge of the diversity of this unique agent. We explore and discuss the potential of sequencing and other effective tools to geographically trace rickettsial disease agents, and develop control strategies to better mitigate the rickettsioses.